Colorectal surgeons should be open to modern surgical technologies for challenging cases. Issue 9 (2nd August 2018) - Hamilton, Auerilius E. R.; Stevenson, Andrew R. L.; Warren, Conor D.; Westwood, David A.
Abstract : Today, colorectal surgeons globally are practicing in an exciting era where surgical technologies are constantly emerging. Most of these cutting‐edge technologies are readily available in Australia and New Zealand at present. Thus the 'modern surgeon' should always be defined by this open‐minded attitude towards these new and emerging surgical technologies. This review article highlights current modalities that we have been using in our north‐Brisbane public and private hospitals for cases predicted to be technically challenging using minimally invasive approaches for most of them. We examined the current evidence regarding the following modalities and critiqued their use in clinical practice: lighted ureteric stents, minimally invasive surgery approaches of laparoscopy and robotic surgery, pressure barrier insufflation devices, 3D camera systems, hand‐assist device ports and indocyanine green dye fluorescence angiography. The objective of this review paper is to alert colorectal surgeons to new surgical technologies available to them, to encourage colorectal surgeons' familiarization with these many technologies, and to support evidence‐based consideration for the clinical use of such. These technologies should be supplemental aides to the safe, oncologically adequate and efficient operation that they already routinely perform.